Utilitarianism versus Universalism in Dangarembga's Nervous Conditions (Nordic Journal of African Studies, 2005)
In her widely acclaimed novel, Nervous Conditions, Tsitsi Dangarembga has used irony with such artistic finesse that many readers seem to miss the subtle indirect satire ranged against Tambudzai, the narrator and implied author of the novel. Tambudzai, the sixteen-year old girl from whose point of view the story is told, is an innocent but unreliable narrator. She misinterprets the facts not purposely, but naively. However, the narrator’s presentational style of her thoughts and feelings is so compelling and honest that she wins the general sympathy of the readers. In fact, her narrative voice has such a ring of truth that some readers have assumed that she necessarily represents the views of the author. This wrong-headed assumption has often misled readers into neglecting what I think is the primary and timeless statement of the novel. The impetus of this article is to show that in Nervous Conditions Dangarembga uses the subject of sexual and colonial domination to invite readers to reflect on two contending philosophies of life: universalism, adopted by Nyasha, and utilitarianism to which all the other characters subscribed.